The inflation function in the Sudanese economy for the period (1992-2022) - Algzoli, Ebtihag Hashim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
The study aimed to know the most important macroeconomic variables that affect the inflation function in Sudan by testing them quantitatively during the period 1992-2022. The results of the study concluded that the phenomenon of inflation in Sudan is a monetary phenomenon, that is, there are internal economic factors such as the money supply and external factors, the exchange rate, and non-economic factors that contribute to increasing inflation, such as government policies, civil wars, and population growth. There are also economic factors that affect inflation and are not included. In the model external debt and imported inflation. In general, it is not possible to rely on the linear equation in representing the inflation function in Sudan, because the coefficients of the independent variables have not been statistically significant because there is a level of significance more than 0.05, and the negative sign of deficit financing is contrary to the data of economic theory. The model suffers from the problem of linear correlation between the independent variables. One of the most important recommendations of the study is version control. Cash and the amount of money, price control, and the Central Bank raising the reserve ratio on bank deposits.